Penerapan Model PBL Untuk Meningkatkan Hasil Belajar Pak pada Siswa Fase D SMP Negeri 4 Botomuzoi Kecamatan Botomuzoi Kabupaten Nias Sumatera Utara - Elisama Laia (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This Classroom Action Research (CAR) aims to enhance the learning outcomes of Catholic Religious Education (CRE) for seventh-grade students in Phase D at SMP Negeri 4 Botomuzoi, Nias Regency, through the implementation of the Problem-Based Learning (PBL) model. The research is motivated by the desire to improve the quality of CRE instruction and student learning outcomes, particularly on the topic "I Am the Unique Image of God." The research employs a descriptive analytical method, with data collection through direct observation, summative assessments (multiple-choice questions), and literature review. The results indicate an average student score improvement from 77.5 in Cycle I to 83.8 in Cycle II, reflecting an increase of 6.3 points. The implementation of the PBL model has proven effective in enhancing students' CRE learning outcomes, demonstrating that the PBL model, supported by audio-visual media, can improve students' understanding and academic performance. This research has positive implications for students, teachers, and schools in efforts to enhance the quality of CRE education.